Paraparetic Guillain‐Barré syndrome: Nondemyelinating reversible conduction failure restricted to the lower limbs. Issue 2 (28th November 2016) - Kimachi, Takeshi; Yuki, Nobuhiro; Kokubun, Norito; Yamaguchi, Shuhei; Wakerley, Benjamin R.
ABSTRACT: Introduction : Paraparetic Guillain‐Barré syndrome (GBS) is a rare subtype of GBS characterized by leg weakness and areflexia in the absence of neurological involvement of the arms, cranial nerves, or respiratory muscles. Onset is characterized by lower back, buttock, or leg pain, followed by development of symmetric flaccid limb weakness in the absence of sensory disturbance. Methods : We describe an elderly woman who developed postinfectious symmetric flaccid leg weakness in the absence of sensory disturbance. Serial nerve conduction studies were carried out over 5 months. Results : Antecedent infection, a monophasic disease course, and the presence of cerebrospinal fluid albuminocytological dissociation suggested a diagnosis of paraparetic GBS. Serial nerve conduction studies demonstrated nondemyelinating reversible conduction failure, which was restricted to the legs. Axonal neuropathy was supported by the presence of anti‐GM1 IgG antibodies. Conclusions : These findings suggest that patients with paraparetic GBS have axonal neuropathy, which is restricted to the lower limbs. Muscle Nerve 55 : 281–285, 2017